A practice framework to enhance the implementation of the Policy on Integration of Mental Health Care into primary health care in KwaZulu-Natal province - Esther N. Hlongwa; Maureen N. Sibiya (AOSIS, 2019)
Background: Mental health care at primary health care (PHC) still remains a challenge despite the Policy on Integration of Mental Health Care into PHC which was developed in 1997 at the time when the White Paper for the Transformation of the Health System in South Africa was published. The White Paper made provision for a new health care system based on the principles of the PHC approach to care. This was followed by the promulgation of the Mental Health Care Act No. 17 of 2002 which is based on the principle that mental health care should be integrated into PHC; however, there have been challenges with regard to the implementation of this policy. Aim: This study aimed to analyse the implementation of Policy on Integration of Mental Health Care into PHC with the ultimate aim of developing a practice framework for PHC nurses to enhance such implementation in KwaZulu-Natal (KZN). Setting: The study took place in selected health districts in KZN, namely, Ugu, eThekwini, iLembe and uMgungundlovu. Methods: A qualitative approach using grounded theory design was used to develop a practice framework to enhance the implementation of Policy on Integration of Mental Health Care into PHC. A theoretical sampling method was used to select the sample from PHC managers, operational managers and professional nurses for the collection of data. The sample consisted of 42 participants. Data were collected by means of one-on-one interviews and focus group interviews. Strauss and Corbin's approach of data analysis was used for analysing data. The paradigm model was used as a guide to develop a practice framework to enhance the implementation of the Policy on Integration of Mental Health Care into PHC in KZN. Results: This study found that integration of mental health care into PHC is understood as a provision of comprehensive care to mental health care users using either a supermarket approach or a one-stop-shop approach at PHC clinics. Strategies that are used at PHC clinics in KZN ensure that the integration of mental health care into PHC is implemented, includes the screening of all patients that come to the PHC clinic for mental illness, fast tracking of mental health care users once they have been assessed, and found to be mentally ill and management of all mental health care users as patients with chronic diseases. Conclusion: The practice framework developed identifies comprehensive mental health care being offered to mental health care users using either a supermarket approach or a one-stop-shop approach, depending on the availability of staff with a qualification in psychiatric nursing science.